Students’ behavioral, emotional, and cognitive engagement in online speaking classes - Diah Palupi; Hasti Robiasih; Titi Lestari; Novita Sumarlin Putri (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This study aims to identify students’ engagement in online speaking class of the eight grader students in one of junior high school in Yogyakarta. Students’ engagement were analyzed using  three main dimension: behavioral, emotional, and cognitive engagement. This study used qualitative method with a case study design. The data were gathered through observations, semi-structured interviews and documentation. Then, the data were analyzed using Miles et al. (2014) theory involving four steps: data collection, data display, data display, conclusion drawing and verification as well as data triangulation among observations, interviews, and observations. The findings reveal that students’ behavioral engagement had a high level as reflected in their active participation, punctuality, attention, and efforts in completing tasks. Emotionally, students show excellent motivation and willingness to follow the class activities, although some students experienced anxiety and fear of making mistakes while speaking English. Furthermore, the cognitive engagement reflected in students’ ability in understanding the materials, asking questions, delivering opinions as well as applying independent learning strategies. Overall, these three dimensions indicate that online speaking learning can remain effective when supported by students’ internal motivation and teacher guidance.